Practical Experience of Endoscope Reprocessing and Working-Platform Disinfection in COVID-19 Patients: A Report from Guangdong China during the Pandemic - Xianqi Lin; Zhenyi Zhang; Minzhao Gao; Zhenling Zhang; Zhidong Lin; Siwen Huang; Jiangnan Ren; Meijuan Luo; Xiaoqing Xu; Guilan Chen; Hongjun Chen; Renxu Lai; et al. (Gastroenterology Research and Practice)
Background. No consensus exists regarding which procedures should be performed to disinfect endoscopes and working platforms after COVID-19 patients have undergone endoscopy. Methods. We analyzed the disinfection quality of endoscopes and working platforms after 11 COVID-19 patients had undergone endoscopy. Conclusions. For endoscopic preprocessing at the bedside, a key disinfection step is using a multienzyme stock solution. The nucleic acid tests for endoscopists, washers, endoscopes, and working platforms were all negative. Based on our experience with the 11 COVID-19 patients who had undergone endoscopy, we provide an endoscopic reprocessing method for the bedside endoscopic diagnosis and treatment of COVID-19 patients for reference.